Building Bridges: The Effects of Having an Adult Learner in a Language Class - BATAKLAR, SİNAN; BAHADIR, AYGÜL (İstanbul Kültür Üniversitesi, 2023)
The purpose of the study is to analyse the effects of having an adult learner in a language class. The study was conducted in a university Preparatory Class (EPC) and was carried out with 4 EPC instructors, 5 EPC students and 1 adult learner (AL). The EPC instructors’ ages are between 36-49 and their teaching experiences are from 10 years to 24., the EPC students’ ages are between 19-21 and the adult learner is 42 and has a PhD in education. The research was designed using the convenience and purposive sampling approach. The data was collected using open-ended questions and the phenomenology technique, which is one of the qualitative research methodologies employed. The data was analysed using the qualitative content analysis approach. Based on the data analysis, noteworthy themes regarding having adult learners in a language class were discovered. The following are the themes and sub-themes: ‘challenges in having an adult learner during language learning process’ contains the sub-themes of bias to language learning, dominance of the adult learner in classroom interaction, the theme ‘benefits of having adult learner in a language class’ contains the sub-themes of motivation, raising language learning awareness, adult learner’s being a role model, knowledge transfer, career planning and the theme ‘the effects of having an adult learner in language learning process’ contains transfer of experience, strategy training, lesson planning and material design.
Köprüler İnşa Etmek: Bir Dil Sınıfında Yetişkin Öğrenenin Etkileri
Keywords: Adult Learner; Language Learning; Motivation; Class Management; In-class Interaction